Analisis Kualitatif Peran Kelompok UMKM dalam Meningkatkan Kinerja dan Daya Saing Usaha di Sektor Ekonomi Lokal - Jendra Satria Pitoyo; Sudaryatno (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are individual business entities or economic actors engaged in economic activities. The research was conducted in Pedaleman Village, Tanara District, Serang Regency. Geographically, the area is a coastal region and has a leading sector, namely fishpond farming. The purpose of this research is to foster synergy among business actors in Pedaleman Village who have not been well mobilized, thus requiring the formation of MSME groups. The method used in this research is a qualitative method utilizing the Focus Group Discussion (FGD) approach and snowball sampling technique due to the incomplete and hard-to-reach population. The research results indicate the need to continuously develop the performance and competitiveness of businesses in the local sector through the smallest regional scale, namely the village, in the form of specific groups, particularly through the formation of Pedaleman MSME Group. This group will serve as a communication channel between the local government and the village, particularly in the local economic sector. Issues such as capital, marketing strategies, packaging, and information can be resolved through the formation of this group. Through the group, benefits can be achieved, such as establishing communication between village-level MSME groups and the local government, specifically the Department of Cooperatives, Industry, and Trade of Serang Regency. It is hoped that this research can serve as a starting point for development and contribute to the revenue of Serang Regency, as well as a means to enhance the quality of business actors through weekly training and participation in regional-scale activities as the practical application of the knowledge gained from the training.